2014
DOI: 10.1371/journal.pone.0099294
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Interaction with Glutamate Receptor Gene GRIN2A: Parkinson's Disease in Swedish Population

Abstract: A complex interplay between genetic and environmental factors is thought to be involved in the etiology of Parkinson's disease (PD). A recent genome-wide association and interaction study (GWAIS) identified GRIN2A, which encodes an NMDA-glutamate-receptor subunit involved in brain's excitatory neurotransmission, as a PD genetic modifier in inverse association with caffeine intake. Here in, we attempted to replicate the reported association of a single nucleotide polymorphism, GRIN2A_rs4998386, and its interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
(21 reference statements)
4
26
0
Order By: Relevance
“…Caffeine intake has been associated with a lower risk of developing PD 1, 2 , and an interaction of this association with GRIN2A genotype has been reported in two prior studies 11, 12 , although this was not replicated in a third study 13 . Two prior studies indicated a deleterious interaction between caffeine and creatine, with higher rates of progression of PD among subjects taking creatine who also had high caffeine intake 7, 8 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Caffeine intake has been associated with a lower risk of developing PD 1, 2 , and an interaction of this association with GRIN2A genotype has been reported in two prior studies 11, 12 , although this was not replicated in a third study 13 . Two prior studies indicated a deleterious interaction between caffeine and creatine, with higher rates of progression of PD among subjects taking creatine who also had high caffeine intake 7, 8 .…”
Section: Discussionmentioning
confidence: 92%
“…Adenosine A2a receptors enhance NMDA-induced calcium influx, and caffeine is an A2a receptor antagonist, providing a potential mechanistic link between caffeine and GRIN2A . Two studies have found that the T-allele of the GRIN2A single nucleotide polymorphism (SNP) rs4998386 strongly influences the association of caffeine with the risk of PD 11, 12 , although this association was not replicated in a third study 13 . In the initial paper by Hamza et al 11 , among heavy coffee drinkers, carriers of a GRIN2A T allele had a 59% lower risk of PD compared to light coffee drinkers.…”
Section: Introductionmentioning
confidence: 99%
“…Early genome-wide associational studies suggested that GRIN2A, but not GRIN2B, was a modifier gene for Parkinson's disease (Hamza et al, 2011;Lee et al, 2011;Yamada-Fowler et al, 2014). Although a large genome-wide associational study did not correlate epilepsy to any of the NMDA receptor genes (International League Against against Epilepsy Consortium on Complex Epilepsies, 2014), the first potential disease-causing mutations in NMDA receptors were described by Endele et al (2010) in GRIN2A, the gene encoding the GluN2A subunit of the NMDA receptor.…”
Section: Gaba/glutamate Receptor Mutations In Neurologic Diseasesmentioning
confidence: 99%
“…This could induce decreased Ca2 1 influx through the cation channel, potentially leading to increased survival through suppression of cell death via apoptosis (excitotoxicity). 117,118 This result was replicated in a Swedish study, 119 but not in a pooled analysis of independent studies targeting populations from Denmark, Sweden, and the USA. 115 CMM patients with nonsynonymous GRIN2A mutations have a more aggressive course with fast progression and shorter survival compared with noncarriers.…”
Section: Cdkn2amentioning
confidence: 93%